E2F-1 as an anticancer drug target - Joseph R. Bertino; Debabrata Banerjee (Frontiers Media S.A., 2011)
Mounting evidence indicates that the E2F transcription factors play an essential role in all aspects of cellular functions. Many human malignancies have been shown to overexpress one or more of the ''activating'' E2Fs. In some circumstances, down regulation as well as overexpression of E2F-1, leads to inhibition of cell growth. The emphasis in this review is placed on new data implicating microRNAs in the regulation of E2F activity and the efforts thus far to target this activity in order to cause tumor regression.